TP53 mutation p.R337H in gastric cancer tissues of a 12-year-old male child - evidence for chimerism involving a common mutant founder haplotype: case report - Prolla Patricia A; Montagnini André L; Olivier Magali; Martel-Planche Ghyslaine; W Achatz Maria; da Silva Edaise M; Hainaut Pierre; Soares Fernando A (BMC Cancer, 2011)
Abstract Background Gastric adenocarcinoma is rare in children and adolescents, with about 17 cases under age 21 in the world's literature. We report a case of invasive well-differentiated metastatic gastric cancer in a Brazilian 12-year-old boy without documented familial history of cancer. Case presentation The patient, diagnosed with metastatic disease, died seven months after surgery. DNA from intra-surgical specimens revealed a TP53 mutation at codon 337 (p.R337H) in samples with neoplastic cells (dysplasia, tumor and metastasis) but not in non-transformed cells (incomplete intestinal metaplasia and non-involved celiac lymph node). In all mutation-positive tissues, p.R337H occurred on the same background, a founder allele identified by a specific haplotype previously described in Brazilian Li-Fraumeni syndrome patients. The same mutant haplotype, corresponding to a founder mutation present in 0.3% of the general population in Southern Brazil, was found in the genome of the father. Presence of this inherited haplotype in the tumor as well as in the father's germline, suggests a rare case of microchimerism in this patient, who may have harbored a small number of mutant cells originating in another individual, perhaps a dizygotic twin that died early in gestation. Conclusion This case represents one of the earliest ages at diagnosis of gastric cancer ever reported. It shows that cancer inheritance can occur in the absence of an obvious germline mutation, calling for caution in assessing early cancers in populations with common founder mutations such as p.R337H in Southern Brazil.